(untitled) (Journal of Politics and International Studies, 2023)
The objective of this research paper is to conduct a comparative analysis of the strategic interests that Saudi Arabia and Iran possess in Syria and Yemen. The objective of this study is to examine the factors that motivate individuals to engage in these wars by a thorough evaluation of academic sources, official declarations, and geopolitical occurrences. The investigation focused on historical connections, sectarian dynamics, and geopolitical strategies to enhance comprehension of the variations in their approaches. An analysis of the Middle East reveals several complex dynamics, including the rivalry between Saudi Arabia and Iran. Both primary and secondary data are collected to comparative the interest of Iran and Saudi Arabia in Syria and Yemen. Primary data are collected through interview and the secondary data are collected from research journals and other published materials. The findings provide valuable insights that can be employed by policymakers, analysts, and researchers to enhance their comprehension of the escalating power struggles and conflicts in the region. To effectively traverse the intricate geopolitics of the Middle East, it is crucial to apply a strategic approach that considers the subtle details.